Adverse Events ‒ One of the Most Important Health Care Quality Indicators: A Case Study - Vinsas Janusonis (European Scientific Journal, ESJ, 2017)
The aim of study: to evaluate inpatients, experienced adverse events (AE) in Klaipeda university hospital (KUH) contingent, healthcare profiles, location and causal factors, the degree of risk, possibility to avoide its, and to compare assessment of doctors and experts, and estimate their changes in different analyzed periods. Material and methods. The study carried out by analyzing the AE reporting forms in KUH at 2000-2014time period. Exploring and comparing 1690 patients, experienced AE data by age, gender, health care profile, the reasons. Results. The survey showed that AE was 0.3 % of hospitalized patients, most of them (54.9 %) ‒ associated with surgery. The largest group of AE ‒ repeated operations (44.8 %), related to childbirth AE (26.2 %) and related to infection ‒ (13.1 %). Almost half (43.2 %) AE were medium risk, one-third (33.8 %) ‒ minimal and one-fifth (21.6 %) ‒ high risk. Doctors (nurses) and experts opinions on the major causative factors of AE ‒ the individual characteristics of the patients (88.5 % and 90.3 %) basically was similar. However, due to the individual characteristics of doctors (nurses) ‒ experts often (14.2 %) could see them as causal factor than doctors or nurses (9.8 %). Due possibility of AE avoidance ‒ doctors (nurses) and experts opinion that almost half of them (44.7 % and 48.8 %) were avoidable was the same, but stood for full possibility of avoidance (11.2 % doctors (nurses) and 16.9 % experts) and complete inevitability (44.1 % doctor (nurses) and 34.3 % experts) of AE. Conclusions: Long-term operating adverse events reporting and registration system and analysis showed that adverse events in KUH is much less than in comparable large multiprofile hospitals of other countries. The structure of AE have advantages with structure in other countries ‒ the most adverse events related to surgery, infections, nursing, but there are significant differences ‒ reported little adverse events related to drugs, diagnostics, and a small number of falls compared with many births related AE. The majority ‒ almost four fifths of the AE was minimal or medium risk, one-fifths ‒ high-risk. The AE related with deaths were few. The main causal factors of AE ‒ individual characteristics of the patients and the doctors, and team work failure. A twothirds of AE could be fully or partially prevented.